Profiles of mothers who seek treatment for substance use disorders in a clinical centre. Issue 1 (25th November 2019) - Fernandez-Montalvo, Javier; López-Goñi, José J.
Abstract : Purpose: The purpose of this paper is to explore the prevalence and profile of mothers among women who sought treatment for drug addiction, as well as the therapeutic progression of these patients. Design/methodology/approach: A sample of 180 Spanish women with addiction problems was assessed. Information was collected on the patients' socio-demographic characteristics, consumption variables and psychological symptoms. Findings: Of the total sample, 22.2 per cent ( n = 40) of the women seeking treatment for substance use disorder were mothers. Compared with women without children, mothers scored significantly higher on several EuropASI and psychological variables. Specifically, mothers presented with more medical problems, worse employment/financial situations, and more severity in alcohol use. Moreover, having a history of lifetime physical and/or sexual abuse was related to belonging to the group of mothers. Regarding therapeutic progression, no statistically significant differences in the retention rate were found between mothers and non-mothers. Originality/value: The results of this study show that mothers generally have more severe problems than non-mothers. Therefore, comprehensive, continuum-based, and client-centred care for mothers is paramount for effective treatment in mothers. The implications of these results for further research and clinical practice are discussed.